Kerusuhan Anti Tionghoa di Semarang Tahun 1980 - Wigarani, Lenisa; Bain, Bain; Witasari, Nina (Journal of Indonesian History, 2019)
The events of anti-Chinese riots in Semarang were riots that began in the city of Solo. The riots that hit the city of Semarang took place in 1980. Therefore, the researcher wants to analyze three problems rising from that background which are: (1) the trigger factor for the anti-Chinese riots in Semarang in 1980, (2) the chronology of anti-Chinese riots in Semarang in 1980, (3) the impact of anti-Chinese riots in Semarang in 1980. In this study the researcher uses a history research method consisting of primary and secondary source. The primary source is the archive source regarding the history of events obtained from the archive data at Depo Arsip Suara Merdeka, (BPS) Badan Pusat Statistik Provinsi Jawa Tengah, and KOMPAS. The researcher also conducted interviews with living witnesses relate to the riots. While secondary sources used are from books or journal related to research. Based on the research result, the researcher stated that the events of anti-Chinese riots that occurred in Semarang in 1980 were the worst inter-ethnic events in the history of the city of Semarang. Anti-Chinese riots caused considerable and serious chaos for the people of Semarang, especially the Chinese people who were affected by the casualties ranging from victims of minor injuries, serious injuries, and the destruction of buildings and transportation vehicles belonging to ethnic Chinese descendants. Keywords: Anti Chinese Riots, in 1980, Semarang.